2000
DOI: 10.1002/(sici)1097-4644(20000201)76:2<217::aid-jcb6>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static or dynamic mechanical stresses on osteoblast phenotype expression in three‐dimensional contractile collagen gels

Abstract: Studies performed at tissular (three-dimensional, 3-D) or cellular (two-dimensional, 2-D) levels showed that the loading pattern plays a crucial role in the osteoblastic physiology. In this study, we attempted to investigate the response of a 3-D osteoblastic culture submitted to either no external stress or static or dynamic stresses. Rat osteosarcoma cells (ROS 17/2.8) were embedded within collagen type I lattices and studied for 3 weeks. Entrapment and proliferation of cells within the hydrated collagen gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…However, the application of mechanical loads has a beneficial effect on the quality and quantity of in vitro generated bone tissues. For example, a study on mechanical loading on osteoblasts in three-dimensional collagen scaffolds under mechanical stress reported that static forces increased cell proliferation and promoted the expression of osteoblastic differentiation markers, such as alkaline phosphatase and osteocalcin [151]. Alternatively, dynamic stresses enhanced the osteocalcin expression but inhibited cell growth and alkaline phosphatase expression [151].…”
Section: Applications Of Nanotopography To Tissue Engineering and mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of mechanical loads has a beneficial effect on the quality and quantity of in vitro generated bone tissues. For example, a study on mechanical loading on osteoblasts in three-dimensional collagen scaffolds under mechanical stress reported that static forces increased cell proliferation and promoted the expression of osteoblastic differentiation markers, such as alkaline phosphatase and osteocalcin [151]. Alternatively, dynamic stresses enhanced the osteocalcin expression but inhibited cell growth and alkaline phosphatase expression [151].…”
Section: Applications Of Nanotopography To Tissue Engineering and mentioning
confidence: 99%
“…For example, a study on mechanical loading on osteoblasts in three-dimensional collagen scaffolds under mechanical stress reported that static forces increased cell proliferation and promoted the expression of osteoblastic differentiation markers, such as alkaline phosphatase and osteocalcin [151]. Alternatively, dynamic stresses enhanced the osteocalcin expression but inhibited cell growth and alkaline phosphatase expression [151]. Tanaka et al also reported that mouse osteoblasts seeded in three-dimensional collagen scaffold under a uniaxial mechanical strain reduced the proliferation rate, while the expression of osteocalcin was increased [152].…”
Section: Applications Of Nanotopography To Tissue Engineering and mentioning
confidence: 99%
“…Different factors are identified as directing the osteoblast behavior. Among these, a low oxygen tension is understood to promote the osteoblastic differentiation [5] and the presence of mechanical stress is described to modulate the osteoblast proliferation [6] and phenotype [7,8] . Additionally, the fibrillar feature of the collagen network appears crucial since it allows the osteoblasts adhesion via integrin α1β1 and α2β1 [9,10] , favors the physiological-type shape and directs cells toward osteoblast maturation by changing the local topography [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that the mechanical stimulus could be as effective as the chemical one to induce bone cell differentiation [134]. Akhouayri and co-workers [135] evaluated the effect of contractive forces onto ROS 17/2.8 osteosarcoma-derived cells. Different contractile conditions were reached in type I collagen gels (freely retracted gels, stretching of the tense gel, periodic stress).…”
Section: Bioreactors Applied To Bone Tissue Engineeringmentioning
confidence: 55%